Multi-omics insights into beagle dog fed with a sucking-rewarded automatic feeding device - Jiao, Yang; Wang, Xin; Yu, Aizhen; Wu, Li; Li, Hongping (Frontiers in Pediatrics, 2024)
Facilitating the development of the sucking function in early stages of preterm infants holds substantial potential for influencing their long-term outcomes. To this end, our team has devised a sucking-rewarded automatic feeding device specifically tailored for preterm infants.The present study is designed to investigate the impacts of this innovative device, utilizing a multi-omics profiling approach, on beagle dogs as a surrogate model.This study involved seven-day-old male newborn beagle puppies, carefully selected and matched in terms of body weights. The participants were stratified into two groups: the experimental group (AFG, sucking-rewarded feeding group) and the control group (PFG). After a 14-day intervention period, fecal and blood samples were systematically collected from each dog. The collected samples were then subjected to distinct profiling analyses, encompassing the assessment of gut microbial composition, plasma metabolic profiles, and proteomic expression profiles.The gut microbial data showed a significant difference between the AFG and PFG groups based on Bray-Curtis dissimilarity (P = 0.048), and the relative abundance of Lactobacillus was significantly more abundant in the AFG group compared to the PFG group. The significantly different metabolites between the two groups were enriched in functional metabolic pathways related to amino acids, fatty acid metabolism, and the nervous system. Notably, neurotransmitter Lglutamic acid was significantly up-regulated in the AFG group. Moreover, the significantly different proteins between the two groups were enriched in GO terms related to oxygen transport, oxygen binding, iron ion binding, hemoglobin complex, and heme binding. Among them, proteins A0A8C0MTD2, P60524, P60529 were significantly up-regulated in the AFG group. Notably, Lactobacillus, L-glutamic acid, A0A8C0MTD2, P60524, and P60529 were correlated with each other through correlation analysis, these molecules play important roles in the neural function and neurodevelopment.Our investigation elucidated discernible modifications in gut microbial composition, plasma metabolic profiles, and proteomic expression patterns in beagle dogs subjected to the sucking-rewarded automatic feeding device.